2011
DOI: 10.1177/147323001103900606
|View full text |Cite
|
Sign up to set email alerts
|

Increased Signal Transducer and Activator of Transcription 3 (STAT3) and Decreased Cyclin D1 in Recurrent Astrocytic Tumours Compared with Paired Primary Astrocytic Tumours

Abstract: This study compared the levels of signal transducer and activator of transcription 3 (STAT3) and cyclin D1 protein in paired primary and recurrent astrocytic tumours, and analysed their correlation with clinicopathological and treatment factors. A total of 48 samples from 24 patients who had undergone surgical removal of primary and recurrent astrocytic tumours were analysed. Levels of STAT3 and cyclin D1 protein were detected using immunohistochemistry. Increased STAT3 and decreased cyclin D1 levels were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Aberrant STAT3 activation is associated with radiation resistance in gliomas. Consistently, in patients with a high risk of recurrence after radiotherapy, there was pronounced STAT3 activation in gliomas (Zhang et al, 2011). As previously described, activation of STAT3 requires phosphorylation of its tyrosine (STAT3-Y705) residue and serine 727 (STAT3-S727) residue.…”
Section: Relationship Between Radiotherapy and Stat3supporting
confidence: 80%
“…Aberrant STAT3 activation is associated with radiation resistance in gliomas. Consistently, in patients with a high risk of recurrence after radiotherapy, there was pronounced STAT3 activation in gliomas (Zhang et al, 2011). As previously described, activation of STAT3 requires phosphorylation of its tyrosine (STAT3-Y705) residue and serine 727 (STAT3-S727) residue.…”
Section: Relationship Between Radiotherapy and Stat3supporting
confidence: 80%
“…This suggests an involvement of STAT3 pathway in glioma progression and a possible link with resistance to treatment. This is strengthened by a report showing that recurrent astrocytic glioma displayed an increased STAT3 protein accumulation compared to primary astrocytic tumors [210].…”
Section: Role Of Stat3 Activation In Glioma Resistance To Standard Trmentioning
confidence: 72%
“…Similarly, another study demonstrated that the levels of JAK2 and STAT3 are significantly upregulated and exhibit pairwise correlation in human glioma tissues (14). The overexpression of constitutively active STAT3 has also been observed to be accompanied by the restoration of cyclin D1 expression (15); however, there is evidence that increased STAT3 and decreased cyclin D1 protein levels may contribute to the recurrence of astrocytic tumors (16). Therefore, the exact regulation of and relationship between STAT3 and cyclin D1 in glioma remains unclear.…”
Section: Introductionmentioning
confidence: 99%